Low cycle fatigue behavior of AZ31B extrusion at elevated temperatures. (October 2020) - Jabbari, A.H.; Sedighi, M.; Jahed, H.; Sommitsch, C.
Highlights: Asymmetric hysteresis loop at room temperature changed to a symmetric one at 200 °C. Hysteresis loops at 200 °C exhibit no inflection point. Twinning-detwinning mechanisms do not govern the plastic deformation at 200 °C. Mean stress diminishes and cyclic softening occurs at the elevated temperatures. Jahed-Varvani model offers the most promising predictions at all the temperatures. Abstract: Fully-reversed strain-controlled tests have been performed on AZ31B magnesium alloy extrusion at room temperature, 100 °C, and 200 °C. Different fatigue life prediction models including Coffin-Manson-Basquin, Smith-Watson-Topper, and Jahed-Varvani were applied to predict the fatigue life. According to the shape of the hysteresis loops at half-life, by increasing the test temperature to 200 °C, the asymmetric behavior of the magnesium changed to a symmetric shape. No inflection point can be observed in the loops at 200 °C, the mean stress decreases dramatically, and the cyclic softening occurs. Among different models, Jahed-Varvani as an energy-based approach offers the most promising predictions at all the temperatures.